PENINGKATAN KEMAMPUAN MENULIS PARAGRAF NARASI MELALUI MEDIA GAMBAR BERSERI PADA SISWA KELAS X SMA YAPIS MANOKWARI TAHUN AJARAN 2016/2017 - Kulsum, Umi; Baru, Yosefina; Tulalessy, Quin D. (JURNAL TRITON PENDIDIKAN, 2017)
This research focus on students ability in writing narrative text using puzzle on X grade student of SMA Yapis Manokwari in academic year 2016/2017 with present two research problem, there are (1) how the students ability in writing naration text of student on X grade SMA Yapis Manokwaribefore using puzzle, (2) how the students ability in writing narative text on X grade of SMA Yapis Manokwari after using puzzle. This research using quantitative methode and using tecnik data text analysis (student work sheet) and data nontest (observation, interview, and documentation). The result of this research can conclude that student ability in writing narative text at precyle with the avarage scor 43,56 with percentage 41,67%, its occur changed cyed I with the avarage scor 69,30 with the percentage 66,67% and increase in the II cyle with the avarage scor 77,91 with the percentage 91,67%.